2016
DOI: 10.3390/ijms17091584
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection, Growth Factors and BDNF-TrkB Signalling in Retinal Degeneration

Abstract: Neurotrophic factors play key roles in the development and survival of neurons. The potent neuroprotective effects of neurotrophic factors, including brain-derived neurotrophic factor (BDNF), ciliary neurotrophic factor (CNTF), glial cell-line derived neurotrophic factor (GDNF) and nerve growth factor (NGF), suggest that they are good therapeutic candidates for neurodegenerative diseases. Glaucoma is a neurodegenerative disease of the eye that causes irreversible blindness. It is characterized by damage to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
130
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(136 citation statements)
references
References 148 publications
(174 reference statements)
1
130
0
5
Order By: Relevance
“…These included, besides CDKN2A and CDKN2B , developmentally relevant genes, CDKN1B , FGF2 , SOX11 , FOS , JUNB , STAT1 , STAT3 , VEGF , BDNF , SCNG, and ATF3 . Of these, the majority is involved in RGC development/survival/regeneration such as FGF2 , SOX11 , SNCG , STAT3 , VEGF , BDNF , and ATF3 . Other common genes included CEBPB , CP , FAS , EDNRB , ANXA1 , NEFL , TP53 , TXN , TXN2 , TBK1 , SOD1 , and OPTN .…”
Section: Resultsmentioning
confidence: 99%
“…These included, besides CDKN2A and CDKN2B , developmentally relevant genes, CDKN1B , FGF2 , SOX11 , FOS , JUNB , STAT1 , STAT3 , VEGF , BDNF , SCNG, and ATF3 . Of these, the majority is involved in RGC development/survival/regeneration such as FGF2 , SOX11 , SNCG , STAT3 , VEGF , BDNF , and ATF3 . Other common genes included CEBPB , CP , FAS , EDNRB , ANXA1 , NEFL , TP53 , TXN , TXN2 , TBK1 , SOD1 , and OPTN .…”
Section: Resultsmentioning
confidence: 99%
“…For example, neurotrophins, such as brain-derived neurotrophic factor and ciliary neurotrophic factor, protect retinal RGCs in an ONI model. [4][5][6] Also, inhibitors of glutamate receptors, tumor necrosis factor receptors, and nitric oxide synthase may be effective for RGC protection. …”
mentioning
confidence: 99%
“…Brain‐derived neurotrophic factor (BDNF) is a neurotrophic factor and exists widely in the central nervous system (CNS), such as the hippocampus and cortex . BDNF plays crucial roles in survival, development, differentiation, and proliferation of brain neurons and repairs of injured nerve cells, which is mediated by the high‐affinity tropomysin‐related kinase B (TrkB) receptor . It has been reported that serum BDNF level is significantly low in depressed and diabetic patients and negatively correlated with the risk of depression .…”
Section: Introductionmentioning
confidence: 99%
“…development, differentiation, and proliferation of brain neurons and repairs of injured nerve cells, 7,8 which is mediated by the high-affinity tropomysin-related kinase B (TrkB) receptor. 9 It has been reported that serum BDNF level is significantly low in depressed and diabetic patients and negatively correlated with the risk of depression.…”
mentioning
confidence: 99%